The Effects of Imprecise Probabilities and Outcomes in Evaluating Investment Options - Du, Ning; Budescu, David V. (Management Science, 2005)
Vagueness attitudes have been used to explain anomalies and irregularities in investment behavior. It is generally assumed (Ellsberg 1961) that decision makers (DMs) dislike vagueness, but this assumption has been challenged by empirical results documenting systematic alternative attitudes to vagueness as a function of its source, the domain of the decisions, and the response mode used. We investigate these three factors in a within-subjects design that was embedded in an investment context. DMs evaluated investment options that varied in terms of their sources of vagueness (probabilities and/or outcomes), in both domains (gains or losses), and employed two response modes (pricing or choice). We confirm that individuals’ vagueness attitudes are malleable, contingent on the dimension salience and the reference domain. In particular, we observed three distinct patterns of “reversals of attitudes” towards vagueness. Our results indicate that the ability of vagueness attitudes to predict investment behavior is limited, as decisions can be systematically influenced by task context and/or perceived gain or loss positions. Economic models may be improved by incorporating more flexible assumptions about individuals’ attitudes toward vagueness.